2006
DOI: 10.2174/157340006776876003
|View full text |Cite
|
Sign up to set email alerts
|

Psychotic (Delusional) Major Depression in the Elderly: A Review

Abstract: The prevalence in the community of psychotic (delusional) major depression (PMD) in the elderly was found to be 1%. In inpatient settings the frequency of the disorder varies between 24% and 53%. There is also evidence that its frequency increases in old age. In the elderly, PMD compared to non-PMD was found to be a more severe and melancholic form of depression with more psychomotor disturbances (agitation or retardation) and feelings of guilt, more anxiety and hypochondriacal complains and less insight. Delu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 55 publications
1
11
0
3
Order By: Relevance
“…La prevalencia de depresión psicótica es variable: 15 a 20% en población general 24 y 24 a 53% en hospitalizados 25 ; por tanto, nuestras cifras (32,1%) son aceptables por tratarse de episodios graves y atención especializada. Pero estos síntomas psicóticos también podrían constituir señales de una posible depresión bipolar.…”
Section: Discussionunclassified
“…La prevalencia de depresión psicótica es variable: 15 a 20% en población general 24 y 24 a 53% en hospitalizados 25 ; por tanto, nuestras cifras (32,1%) son aceptables por tratarse de episodios graves y atención especializada. Pero estos síntomas psicóticos también podrían constituir señales de una posible depresión bipolar.…”
Section: Discussionunclassified
“…Studies have found that the frequency of psychotic depression in people over age 60 in inpatient settings varies between 24% and 53%. 17 …”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…PD is classified as a subtype of severe unipolar depression/severe depression in bipolar disorder in the two current major diagnostic systems, namely the 10th revision of the International Classification of Disease (ICD-10) [1] and the 4th edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV) [2]. PD is prevalent [3,4], underdiagnosed [5], undertreated [6] and has a high morbidity and mortality [7,8,9], but has received disproportionally little attention compared with other less prevalent and less severe mental disorders [10]. …”
Section: Introductionmentioning
confidence: 99%
“…F20.0 for paranoid schizophrenia) and that the majority of these were used very rarely. The number of diagnostic syndromes should obviously be kept to a reasonable minimum, but since PD is a rather prevalent disorder [3,4,10] and already defined in the diagnostic manuals, this argument seems misplaced in the discussion of defining PD as a distinct diagnostic syndrome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation